Fabrication of sustainable hydrogels-based chitosan Schiff base and their potential applications - Taghreed H. Abdalla (Elsevier, 2022)
Chemical modifications of chitosan were of interest to scientific researchers for its wide applications. Chitosan has been widely used for synthesis of unique compounds with potential biological activity and also effective for wastewater treatment. In the current study fabrication of new chitosan-based Schiff base hydrogels were fabricated through modification of chitosan with isonicotinic aldehyde to give hydrogel I or with epichlorohydrin or sodium tripolyphosphate via ionotropic gelation processes under the same reaction conditions to give hydrogels Ie, and nanohydrogels II, IIe respectively. FTIR, XRD, TGA, DSC, SEM, and TEM tools were used for characterization of the fabricated hydrogels I, Ie, II, and IIe hydrogels. The swelling behavior of the fabricated hydrogels in different solvents were determined. Evaluation of the hydrogels for leaching metal ions and biological activity towards different Gram-positive and Gram-negative of microorganisms were studied. The results showed that the highest efficiency for adsorption of cobalt and mercuric ions was revealed for hydrogels Ie, IIe (91.3%, 95.9%) and (92.5%, 95.9%) respectively. However, hydrogel IIe showed remarkable MIC and MBC towards Gram-positive (B. subtilis) (19.5, 38) μg/ml compared to the standard antibiotic Ciprofloxacin (19, 38) μg/ml respectively.